Drying Effect for Amino Acid Composition of Worms Lawar Perinereis cf.cultrifera (BLEEKER 1840) Wearlilir Waters from Kei Islands Maluku Southeast District - Martha Rettob; Nally Erbabley; Santy Rahantoknam (LPPM, Institut Teknologi Sepuluh Nopember, 2016)
The purpose of this study was to determine the effect of drying on the amino acid composition of the worm lawar Perinereis cf.cultrifera (Bleeker 1840) The method used is a natural drying process with artificial sun with electric oven and then analyzed the amino acid composition by GC (Gas Kromotofrafi). Result obtained for the solar drying process there are 14 types of amino acids with the composition: 0.890 mg/g 0.746 mg/g Alanine, 0.096 mg/g Alpha-amino Butyric acid, 2,090 mg/g Valine, 0.088 mg/g amino Beta Isobutyric ACIC, threonine, 0.913 mg/g Aspartic acids, 16,505 mg/g Hydroxyproline, 15,361 mg/g Glutamic acid, 0.581 mg/g Phenylalanine, 2.254 mg/g Alpha-aminoadipic acids, 0.868 mg/g Ornithine, 0.959 mg/g Lysine, 1,209 mg/g histidine, 0.993 mg/g of tyrosine, while the artificial drying (oven) there are 12 types of amino acids which are: 0.673 mg/g Alanine, 0.046 mg/g Glysine, 0.0678 mg/g Alpha-amino Butyric acid, 0.224 mg/g Valine, 2.803 mg/g Threonine, 0.297 mg/g Serine, 0.068 mg/g Methionine, 22,015 mg/g Hydroxyproline, 1.282 mg/g Phenylalanine, 0,782 mg/g Alpha-aminoadipic acids, 0.952 mg/g Ornithine, Lysine 1,049